Evaluation of the turbulence parametrization in the MOLOCH meteorological model. (27th November 2019) - Trini Castelli, Silvia; Bisignano, Andrea; Donateo, Antonio; Landi, Tony C.; Martano, Paolo; Malguzzi, Piero
Abstract: An appropriate parametrization of turbulence is fundamental both in meteorological and atmospheric dispersion models, in order to properly simulate the dynamics of the flow and of the pollutants transported by it. The turbulence closure adopted in the meteorological model MOLOCH is presented, and its reliability and effectiveness are evaluated based on turbulent kinetic energy data measured at two suburban sites in north and south Italy. Very different topographical situations characterise the two sites, an Alpine and a coastal region, respectively. Particular attention is paid in assessing the low‐wind speed regime, a critical condition for air pollution, associated with turbulent features not yet fully understood. The analysis has proved that the turbulence closure in the MOLOCH model is able to capture and effectively reproduce the observed low‐level atmospheric turbulence processes, in all stability conditions. Abstract : The reliability and effectiveness of the turbulence closure adopted in the meteorological model MOLOCH is evaluated, based on turbulent kinetic energy data measured at two suburban sites, characterised by very different topographical situations, an Alpine and a coastal region in north and south Italy, respectively. Low‐wind speed conditions, associated to turbulent features not yet fully understood and critical for air pollution dispersion, are assessed. The MOLOCH model is able to capture and effectively reproduce the observed low‐level atmospheric turbulence processes.